Multi-objective robust energy management for all-electric shipboard microgrid under uncertain wind and wave - Fang, Sidun (2022)
An all-electric ship (AES) uses diesel generators and energy storage system (ESS) to meet both propulsion and service loads. Thus, it can be viewed as a mobile microgrid. During the operation of an AES, significant uncertainties such as water wave and wind introduce considerable speed loss, which may lead to severe voyage delays. To fully address this issue, a new robust energy management model is proposed to coordinately schedule an AES's power generation and voyage considering the uncertain wave and wind. Two objectives are minimized simultaneously: the fuel consumption (FC) and energy efficiency operational indicator (EEOI). The problem is formulated as a bi-level robust optimization model after certain constraint decomposition. Normal boundary intersection method is utilized to solve this multi-objective programming. Compared with existing joint scheduling methods, the proposed method can fully guarantee the on-time rates of AES in various uncertain scenarios and providing high-quality Pareto solutions.